2019
DOI: 10.1063/1.5124677
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electronic structures and transport coefficients of Janus PtSSe monolayer with biaxial strain

Abstract: Due to their great potential in electronics, optoelectronics and piezoelectronics, Janus transition metal dichalcogenide (TMD) monolayers have attracted increasing research interest, the MoSSe of which with sandwiched S-Mo-Se structure has been synthesized experimentally. In this work, the biaxial strain dependence of electronic structures and transport properties of Janus PtSSe monolayer is systematically investigated by using generalized gradient approximation (GGA) plus spin-orbit coupling (SOC). Calculated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…The spin-orbit splitting values in In 2 SSe and In 2 SeTe monolayer are respectively 0.203 eV and 0.304 eV. Previously, the high spin-orbit splitting values have been also found for Janus monolayers PtSSe (0.280 eV) [45] and SnSSe (0.266 eV) [44]. Also, spin splitting of the uppermost valence band in Janus dichalcogenide WSeTe monolayer up to 0.46 eV [46] and high valley spin splitting (0.449 eV) around the K point has been found in WSSe monolayer due to the SOC effect [47].…”
Section: Electronic Propertiesmentioning
confidence: 56%
“…The spin-orbit splitting values in In 2 SSe and In 2 SeTe monolayer are respectively 0.203 eV and 0.304 eV. Previously, the high spin-orbit splitting values have been also found for Janus monolayers PtSSe (0.280 eV) [45] and SnSSe (0.266 eV) [44]. Also, spin splitting of the uppermost valence band in Janus dichalcogenide WSeTe monolayer up to 0.46 eV [46] and high valley spin splitting (0.449 eV) around the K point has been found in WSSe monolayer due to the SOC effect [47].…”
Section: Electronic Propertiesmentioning
confidence: 56%
“…4. 2D Janus materials have attracted extensive attentions due to their unique structure, electronic, and optoelectronic properties [227][228][229]. The formation of Janus crystal structure broke the inversion and mirror symmetry, leading to an intrinsic built-in electric field.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several Janus materials have been developed, such as Janus PtSSe, 34,35 SnSSe 36 and ZrSSe 37,38 monolayers. Guo et al, 37 via rst-principle calculations demonstrated that the Janus ZrSSe monolayer is dynamically and mechanically stable.…”
Section: ) or Selenization Of Mos 2 33mentioning
confidence: 99%